Respuesta :
Answer:
d = 55.5
x = 1
c = 11
m = [tex]\frac{1}{122}[/tex]
k = [tex]\frac{a}{(c + 5)}[/tex]
Step-by-step explanation:
Sorry, the formatting is slightly hard to understand, but I think this is what you meant.
Q1.
[tex]\frac{1}{6}[/tex]d - 8 = [tex]\frac{5}{8}[/tex] x 2
Step 1. Simplify.
[tex]\frac{5}{8}[/tex] x 2 = [tex]\frac{5}{8}[/tex] x [tex]\frac{2}{1}[/tex] = [tex]\frac{10}{8}[/tex]
Step 2. Cancel out the negative 8.
[tex]\frac{1}{6}[/tex]d - 8 = [tex]\frac{10}{8}[/tex]
+ 8 to both sides (do the opposite: [tex]\frac{1}{6}[/tex]d is subtracting 8 right now, but to cancel that out, we will do the opposite of subtraction, i.e. addition)
[tex]\frac{1}{6}[/tex]d = [tex]\frac{10}{8}[/tex] + 8
Step 3. Simplify.
[tex]\frac{10}{8}[/tex] + 8 = [tex]\frac{10}{8}[/tex] + [tex]\frac{8}{1}[/tex] = [tex]\frac{10}{8}[/tex] + [tex]\frac{64}{8}[/tex] = [tex]\frac{74}{8}[/tex] = [tex]\frac{37}{4}[/tex]
Step 4. Cancel out the [tex]\frac{1}{6}[/tex].
[tex]\frac{1}{6}[/tex]d = [tex]\frac{37}{4}[/tex]
÷ [tex]\frac{1}{6}[/tex] from both sides (do the opposite: d is multiplied by [tex]\frac{1}{6}[/tex] right now, but to cancel that out, we will do the opposite of multiplication, i.e. division)
÷ [tex]\frac{1}{6}[/tex] = x 6
So....
x 6 to both sides
d = [tex]\frac{37}{4}[/tex] x 6 = [tex]\frac{37}{4}[/tex] x [tex]\frac{6}{1}[/tex] = [tex]\frac{222}{4}[/tex] = [tex]\frac{111}{2}[/tex] = 55.5
Step 5. Write down your answer.
d = 55.5
Q2.
3x - 4 + 5x = 10 - 2x × 3
Step 1. Simplify
3x - 4 + 5x = 3x + 5x - 4 = 8x - 4
10 - 2x × 3 = 10 - (2x × 3) = 10 - 6x
Step 2. Cancel out the negative 6x
8x - 4 = 10 - 6x
+ 6x to both sides (do the opposite - you're probably tired of reading this now - right now it's 10 subtract 6x, but the opposite of subtraction is addition)
14x - 4 = 10
Step 3. Cancel out the negative 4
14x - 4 = 10
+ 4 to both sides (right now it's 14x subtract 4, but the opposite of subtraction is addition)
14x = 14
Step 4. Divide by 14
14x = 14
÷ 14 from both sides (out of the [14 × x] we only want the [x], so we cancel out the [× 14])
x = 1
Step 5. Write down your answer.
x = 1
Q3.
7(c - 3) = 14 × 4
Step 1. Expand the brackets
7(c - 3) = (7 x c) - (7 x 3) = 7c - 21
Step 2. Simplify
14 x 4 = 56
Step 3. Cancel out the negative 21
7c - 21 = 56
+ 21
7c = 56 + 21
7c = 77
Step 4. Cancel out the ×7
7c = 77
÷ 7
c = 77 ÷ 7
c = 11
Step 5. Write down your answer.
c = 11
Q4.
11([tex]\frac{m}{22}[/tex] + [tex]\frac{3}{44}[/tex]) = 87m + m × 5
Step 1. Expand the brackets
11([tex]\frac{m}{22}[/tex] + [tex]\frac{3}{44}[/tex]) = (11 x [tex]\frac{m}{22}[/tex]) + (11 x [tex]\frac{3}{44}[/tex]) = ([tex]\frac{11}{1}[/tex] x [tex]\frac{m}{22}[/tex]) + ([tex]\frac{11}{1}[/tex] x [tex]\frac{3}{44}[/tex]) = [tex]\frac{11m}{22}[/tex] + [tex]\frac{33}{44}[/tex] = [tex]\frac{m}{2}[/tex] + [tex]\frac{3}{4}[/tex]
Step 2. Simplify.
87m + m x 5 = 87m + 5m = 92m
Step 3. Cancel out the add [tex]\frac{3}{4}[/tex]
[tex]\frac{m}{2}[/tex] + [tex]\frac{3}{4}[/tex] = 92m
- [tex]\frac{3}{4}[/tex]
[tex]\frac{m}{2}[/tex] = 92m - [tex]\frac{3}{4}[/tex]
[tex]\frac{m}{2}[/tex] = [tex]\frac{92m}{1}[/tex] - [tex]\frac{3}{4}[/tex]
[tex]\frac{m}{2}[/tex] = [tex]\frac{368m}{4}[/tex] - [tex]\frac{3}{4}[/tex]
[tex]\frac{m}{2}[/tex] = [tex]\frac{368m - 3}{4}[/tex]
Step 4. Cancel out the ÷ 4
[tex]\frac{m}{2}[/tex] = [tex]\frac{368m - 3}{4}[/tex]
x 4
2m = 368m - 3
Step 5. Cancel out the 368m
2m = 368m - 3
- 368m
-366m = - 3
Step 6. Cancel out the × -366
-366m = -3
÷ -366
m = [tex]\frac{-3}{-366}[/tex]
m = [tex]\frac{1}{122}[/tex]
Step 7. Write down your answer.
m = [tex]\frac{1}{122}[/tex]
Q5.
ck + 5k = a
Step 1. Factorise
ck + 5k = (c × k) + (5 × k) = (c + 5) x k = k(c + 5)
Step 2. Cancel out the × (c + 5)
k(c + 5) = a
÷ (c + 5)
k = a ÷ (c + 5)
k = [tex]\frac{a}{(c + 5)}[/tex]